The Investigation On How Applying An Electric Field For 60 Minutes Affects The Growth Of Specific Bacterial Species: Investigasi Tentang Bagaimana Menerapkan Medan Listrik Selama 60 Menit Mempengaruhi Pertumbuhan Spesies Bakteri Tertentu - Shaban, Abbas Dareb; Aziz, Huda Hassan; Hamadi, Hameed A.; Hamid, Batool Sajad (Indonesian Journal on Health Science and Medicine, 2024)
We discovered that some of them suffered damage to their walls or membranes as a result of the electric field lines flowing through them. Depending on the variation in intensity, bacteria are affected by the field, whether it is positive at most or negative to a small extent, as this laboratory experiment demonstrated. Despite the strength of their walls, we discovered that pathogenic bacteria are affected by an electric current of 60 amps, which caused a modest change in their growth or, more precisely, made them growth-inhibiting in contrast to their pure state. Highlights: Electric fields damage bacterial walls/membranes based on intensity variation. Pathogenic bacteria affected by 60-amp current, inhibiting growth. Growth differs from pure state due to electric exposure. Keywords: electric field, bacterial growth, nutrient agar, Staphylococcus aureus